Applying SEO Methods (On-Page and Off-Page) to Optimize the Ranking of the Top Herbal Atsiri Website - Chelsy Jelita Chinta Putri Herwindo; Endang Sulistiyani (Jurnal Teknologi Informatika dan Komputer, 2026)
Search Engine Optimization (SEO) is an important strategy for improving website rankings in search engines. The website of PT. Unggul Herbal Atsiri, which operates in the herbal health product sector, still does not appear on the first page of Google search results even though it has used relevant keywords such as "telon oil" and "essential oil". This condition indicates a problem in the implementation of SEO strategies that are not optimal, so a more effective approach is needed to improve the website's search performance. This study used On-Page and Off-Page SEO methods, both individually and in combination. The implementation was carried out based on 3 (three) different scenarios and analyzed by considering the results on 2 (two) types of devices, namely mobile and desktop. The results showed that the application of the combination of On-Page and Off-Page SEO methods provided the best results in 2 (two) main parameters, namely increased visitor traffic and website page loading speed. However, in the keyword search ranking parameter, the results were not optimal. Of the 7 (seven) keywords tested, only 1 (one) managed to enter the first page of Google. Thus, the combination SEO strategy has proven effective in certain aspects, but still needs strengthening to improve performance in keyword-based searches. This research is expected to provide more specific and relevant solutions for improving website rankings, both in mobile and desktop search engines, thereby supporting the achievement of effective digital marketing goals.